(1+1/2) elevado 2 - (1-1/2) elevado 2
Soluções para a tarefa
Respondido por
1
Resposta:
2
Explicação passo-a-passo:
(1 + 1 ÷ 2)^2 - (1 - 1 ÷ 2)^2=2
Dê como melhor resposta: )
Respondido por
0
Resposta: 1/8
Explicação passo-a-passo:
vamos lá
( 1 - 1/2)² + (-1 + 1/2)³
= (2/2 - 1/2)² + (1/2 - 2/2)³
= (1/2)² + (-1/2)³
= 1/4 -1/8
= (2 - 1)/8
= 1/8
bons estudos!
Perguntas interessantes
Inglês,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Português,
8 meses atrás
História,
8 meses atrás
Inglês,
1 ano atrás
Português,
1 ano atrás